Has Ecclesiastical History Lost the Plot? - Foot, Sarah (Studies in church history, 2013)
The Ecclesiastical History Society’s fiftieth anniversary conference provides an opportunity both to celebrate the achievements of the society and to reflect on the current state of the discipline. In asking whether church historians have lost the plot, I do not mean to question colleagues’ reason and sanity, but to wonder whether those of us who work in this field might have forgotten some of the objectives and principles that once distinguished our endeavour. Has ecclesiastical history lost its sense of purpose, its place at the heart of historical enterprise, to the extent that it has become not just marginalized and peripheral, but essentially irrelevant both to academic study and wider society?